Site‐ and Stereoselective Phosphoramidation of Carbohydrates Using a Chiral Catalyst and a Chiral Electrophile. Issue 16 (5th July 2019) - Glazier, Daniel A.; Schroeder, John M.; Blaszczyk, Stephanie A.; Tang, Weiping
Abstract: Carbohydrates are the most prevalent class of naturally occurring biomolecules. They mediate cell signaling, bacterial virulence, and metabolism, among other functions. The site‐selective functionalization of carbohydrates has been a long‐standing problem in chemistry. Phosphoramidates are a particularly challenging functional group to install stereoselectively because of the chirality at the phosphorus center. As such, the site‐ and stereoselective phosphoramidation of carbohydrates has never been achieved. We have developed the first site‐ and stereoselective phosphoramidation reaction of carbohydrates using a chiral catalyst and a chiral electrophile. This method offers a convenient solution for the selective synthesis of phosphoramidated carbohydrate‐containing prodrugs and natural products. Abstract :